Quadratics in Japanese - Winsløw, Carl (NOMAD Nordic Studies in Mathematics Education, 2004)
Starting from a description of two lessons on quadratic equations in a junior high school of Tokyo, this paper attempts to throw new light on the principles and philosophies underlying secondary mathematics teaching in Japan. In particular, the paper concludes by discussing their relation to constructivism and structuralism in the Western sense. To put this description in perspective, some examples of analogous Danish conditions are mentioned.